The Kidney Research National Dialogue: Gearing Up to Move Forward - Bonventre, Joseph V. (American Society of Nephrology, 2014)
The National Institute of Diabetes and Digestive and Kidney Diseases–supported Kidney Research National Dialogue asked the scientific community to formulate and prioritize research objectives that would improve our understanding of kidney function and disease; >1600 participants from >30 countries posted >300 ideas and >500 comments covering all areas of kidney research. Smaller groups of investigators interrogated the postings and published a series of commentaries in CJASN. Additional review of the entire series identified six cross-cutting themes: (1) increase training and team science opportunities to maintain/expand the nephrology workforce, (2) develop novel technologies to assess kidney function, (3) promote human discovery research to better understand normal and diseased kidney function, (4) establish integrative models of kidney function to inform diagnostic and treatment strategies, (5) promote interventional studies that incorporate more responsive outcomes and improved trial designs, and (6) foster translation from clinical investigation to community implementation. Together, these cross-cutting themes provide a research plan to better understand normal kidney biology and improve the prevention, diagnosis, and treatment of kidney disease, and as such, they will inform future research efforts supported by the National Institute of Diabetes and Digestive and Kidney Diseases through workshops and initiatives.